Kepemimpinan Beretika dan Kinerja Organisasi: Studi Kasus Indomie di Taiwan dan Hong Kong - Alexander Joseph Ibnu Wibowo (Jurnal Manajemen Maranatha, 2016)
Ethical leadership has emerged as a concept that played a significant part in promoting organizational performance. Based on this background, the purpose of this study is to critically examine the case of withdrawal of circulation of Indomieinstant noodles in Taiwan and Hong Kong. As one of the issues of business ethics in global business, critical analyzes will be viewed from the perspective of ethical leadership. Specifically, this case study will use the findings of previous studies bydesigning a theoretical model, called Integrated Ethical Leadership Model (IEL Model). This model is able to identify the antecedents and consequences of ethical leadership, as well as their implications for organizational performance. This studyis expected to be followed up with a quantitative empirical study to test the accuracy of theoretical models that have been designed.Keywords: Business Ethics, Ethical Leadership, Global Business, Case Study, Indonesia